Investigating the therapeutic potential of hesperidin targeting CRISP2 in intervertebral disc degeneration and cancer risk mitigation - Zhang, Hui; Jiang, Wei; Jiang, Yuqing; Xu, Nanwei; Nong, Luming; Li, Tengfei; Liu, Ruiping (Frontiers in Pharmacology, 2024)
Background: Intervertebral disc degeneration (IDD) can lead to disc herniation and spinal instability, sometimes requiring surgical intervention. Currently, estrogen has a potential protective effect on IDD, and estrogen is associated with an increased risk of some cancers, such as breast and endometrial cancer. Therefore, it is important to identify natural compounds that estrogen analogues treat IDD while reducing the risk of tumor development. Objective: This study aims to explore a natural metabolic treatment strategy by targeting CRISP2 with the natural compound Hesperidin to mimic the protective effects of estrogen on IDD and reduce the risk of tumor development. Methods: Microarray data from healthy volunteers and IDD patients were extracted from the Gene Expression Omnibus (GEO) database, and RNA sequencing and clinical data from various cancer types were analyzed. Differentially expressed genes (DEGs) were identified using the Bioconductor Limma package, followed by principal component analysis, volcano plot, and heatmap visualization. Additionally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses, CIBERSORT and ssGSEA immune cell infiltration assessments, survival analysis, metabolite enrichment analysis, and molecular docking were performed. Hesperidin's interaction with CRISP2 was further validated through molecular docking and experimental studies. Results: Hesperidin significantly reduced the expression of CRISP2, iNOS, and COX2 in IDD models, decreased reactive oxygen species (ROS) and apoptosis, and diminished inflammatory markers. CIBERSORT and ssGSEA analyses revealed a correlation between CRISP2 and immune cell infiltration. Survival analysis demonstrated that CRISP2 expression levels were associated with patient survival across various cancer types. Hesperidin was found to mimic estrogen's effects on IDD and reduce tumor progression. Cell culture and experimental validation confirmed Hesperidin's protective effects on nucleus pulposus cells (NPCs). Conclusions: Hesperidin, as a potential natural metabolic regulator, not only has therapeutic effects on IDD but may also synergize with estrogen therapy to promote spinal health without increasing cancer risk. This study presents a new clinical approach for IDD treatment and lays the foundation for further drug development and experimental research.